1987
DOI: 10.4153/cjm-1987-024-4
|View full text |Cite
|
Sign up to set email alerts
|

MOD-C Postnikov Approximation of a 1-Connected Space

Abstract: Deleanu, Frei and Hilton have developed the notion of generalized Adams completion in a categorical context [4]. They have also shown that if the set of morphisms is saturated then the Adams completion of an object is characterized by a certain couniversai property. We want to prove a stronger version of this result by dropping the saturation assumption on the set of morphisms; we also prove that the canonical map from an object to its Adams completion is an element of the set of morphisms under very moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Proof. The proof follows from the dual of Theorem 1.3 [4]. We take 𝑆 𝑛 1 satisfy all conditions of Theorem 1.2; hence 𝑒 ∈ 𝑆 𝑛 .…”
Section: A Primary Decomposition Of a 0-connected Based Nilpotent Spacementioning
confidence: 99%
See 2 more Smart Citations
“…Proof. The proof follows from the dual of Theorem 1.3 [4]. We take 𝑆 𝑛 1 satisfy all conditions of Theorem 1.2; hence 𝑒 ∈ 𝑆 𝑛 .…”
Section: A Primary Decomposition Of a 0-connected Based Nilpotent Spacementioning
confidence: 99%
“…Given aset S of morphisms of 𝒞, the saturation of S, denoted as S is the set of all morphisms u in 𝒞 such that F(u) is an isomorphism in 𝒞 S −1 . Furthermore,S is said to be saturated if S = S [4,9]. Deleanu, Frei and Hilton have shown that if the set of morphisms Sis saturated then the Adams cocompletion of a space is characterized by a certain couniversal property ( [9],dual of Theorem 1.2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation